Missing Links in Paternal Haplogroup J1-M267. Filling in the J1-M267 Phylogenetic Gap. Two Mesolithic Clades of Human Y chromosome haplogroup J1-M267: J1-FGC6064 and J1-ZS6599. - Costa de Oliveira, Ricardo (Zenodo, 2021)
Abstract: Y chromosome haplogroup J1-M267 has been investigated by many authors in several recent articles and studies, but some important basal branches have not been included or are unknown in previous articles. We are going to investigate the Northern Middle Eastern phylogenetic structure, the spatial and ethnic locations of Human Y chromosome haplogroup J1>M267>FGC6064 and J1>M267>ZS6599 strategic branches for the dispersion of the J1 haplogroup. We study high-coverage whole Y chromosome sequences and results of genotyped specific samples of basal branches of haplogroup J1>M267. Here we are going to add, incorporate and investigate two important phylogenetic basal branches for the entire phylogenetic organization, location, demographic history, development and geography of J1-M267 haplogroup: J1> M267> Z2215> Z2217> L620> FGC6064 and J1> M267> Z2215> Z2217> L620> PF4816> ZS6599. The genotyped samples showed deeply rooted nodes and genetic bifurcations probably related to the existence of an ancient Mesolithic and Neolithic population with an ancient and rich J1-L620 basal diversity of this haplogroup in a mating complex in Northern Middle East and Iran since 15000 years before present (ybp).
Keywords: Y Chromosome. Demographic history. Haplogroup Y-DNA J1-M267. Phylogenetic tree. J1-FGC6064 and J1-ZS6599.